2001
DOI: 10.1071/bt01014
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of salinity stress and the response to temperature in two seed morphs of Halopyrum mucronatum (Poaceae)

Abstract: Halopyrum mucronatum (L.) Stapf. is a coastal dune grass that produces seeds twice during each growing season. Seeds produced during May (summer seed) were black and heavier (2.8 ± 0.09 mg) than brown seeds (2.1 ± 0.04 mg; winter seed) that were produced in November. There was greater than 95% germination in both seed morphs in the non-saline controls at all temperature regimes, but germination was inhibited more by low than high temperatures in the salinity treatments. Summer seeds were more tolerant of salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 29 publications
1
45
0
1
Order By: Relevance
“…acuminatum. Similar trends have been found in many halophytes Ungar 1996a, 1996b;Khan et al 1998;Katembe et al 1998;Ishikawa and Kachi 2000;Khan and Ungar 2001;Khan et al 2003). Moderate (50-200 mM) but higher saline concentration (300 mM) did not significantly inhibit seed germination of E.pilosa, whereas lower salinity (50 mM) significantly increased seed germination percentage of Ch.glaucum.…”
Section: Discussionsupporting
confidence: 68%
“…acuminatum. Similar trends have been found in many halophytes Ungar 1996a, 1996b;Khan et al 1998;Katembe et al 1998;Ishikawa and Kachi 2000;Khan and Ungar 2001;Khan et al 2003). Moderate (50-200 mM) but higher saline concentration (300 mM) did not significantly inhibit seed germination of E.pilosa, whereas lower salinity (50 mM) significantly increased seed germination percentage of Ch.glaucum.…”
Section: Discussionsupporting
confidence: 68%
“…Khan and Ungar (2002) reported that nitrate and thiourea promoted the germination of Zygophyllum simplex seeds at the lowest (25 mM NaCl) salinity but did not promote germination at higher (125 mM NaCl) salinities. Seed germination of Allenrolfea occidentalis and Halopyrum mucronatum, however, is promoted by thiourea in NaCl treatments (Gul and Weber 1998;Khan and Ungar 2001c). Some nitrogenous compounds such as SNP, nitrate, nitrite, and thiourea are known to stimulate the germination of seeds (Esashi et al 1979;Aldosaro et al 1981;Yoshiyama et al 1996;Beligni and Lamattina 2000;Batak et al 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Thiourea significantly alleviated the salinity-induced dormancy in winter seeds of Halopyrum mucronatum (Khan and Ungar 2001a), in Sporobolus arabicus (Khan and Ungar 2001c), but only partially alleviated it in Triglochin maritima (Khan and Ungar 2001b). Nitrogenous compounds are known to promote germination by acidification and softening of cell walls or by activating the pentose phosphate pathway (Esashi et al 1979).…”
Section: Discussionmentioning
confidence: 95%
“…Kinetin and GA 3 partially alleviated the germination inhibition at higher salinity (600 mM NaCl) in P. juliflora. Both these compounds are known to alleviate the salinity-induced germination inhibition in Brassica campestris (Ozturk et al 1993), Zygophyllum simplex (Khan and Ungar 1997), Halopyrum mucronatum (Khan and Ungar 2001a), Atriplex halimus (Debez et al 2001), Salicornia rubra . There was a partial alleviation in salinity induced dormancy by kinetin in Triglochin maritima (Khan and Ungar 2001b) and by GA 3 in Salicornia pacifica (Khan and Weber 1986).…”
Section: Discussionmentioning
confidence: 97%